1
$\begingroup$

Hello I have following problem: solve equation $\log{(x-5)^2}+\log{(x+6)^2}=2$

and I rewrited this equation as

$2\log{(x-5)}+2\log{(x+6)}=\log{100} \implies 2(\log{(x-5)(x+6))=\log{100}} \implies \log{x^2+x-30}=\log10 \implies x^2+x-40=0 $

and I solved this equation, but I obtained only two solutions and there should be four, so I wonder if it is necessary to create $\log{(x-5)^2(x+6)^2}=\log{100}$ or is a simplier way.

$\endgroup$
  • $\begingroup$ I assume the question specifies the base of log is $10$? $\endgroup$ – Macavity Dec 1 '13 at 15:15
  • $\begingroup$ yes of course . $\endgroup$ – Mark Dec 1 '13 at 15:16
2
$\begingroup$

$$\log{(x-5)^2}+\log{(x+6)^2}=2$$ $$\log{((x-5)(x+6))^2}=2$$ $$((x-5)(x+6))^2=10^2=100$$ $$(x-5)(x+6)=\pm10$$Solve from here

$\endgroup$
1
$\begingroup$

As the logarithm term contains squares, we can allow $x-5,x+6$ to be negative

In fact, $\log b^2=2\log |b|$ for real $b$

As $\log A+\log B=\log (AB),$

$$\implies \log_{10}\{(x-5)(x+6)\}^2=2$$

$$\implies \{(x-5)(x+6)\}^2=10^2=100$$

$$\implies (x-5)(x+6)=\pm10$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.